2021
DOI: 10.3233/jpd-202407
|View full text |Cite
|
Sign up to set email alerts
|

Digital Therapeutics in Parkinson’s Disease: Practical Applications and Future Potential

Abstract: Digital therapeutics, treatments delivered remotely and enabled by modern technology, facilitate the provision of personalized, evidence-based, interdisciplinary interventions to manage the complexities associated with Parkinson’s disease. In the context of the COVID-19 pandemic, the need for digital therapeutics has arguably never been greater. However, despite new advances in technology and a heightened interest due to the pandemic, digital therapeutics remain underdeveloped and underutilized. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…The fact that confinement and reduced medical services affect psychiatric health [3] but may also worsen progression of chronic diseases such as PD has consequences for the decision-making process of lawmakers and governmental bodies. Further, whilst treatments for improving functional outcomes through telemedicine offer opportunities to treat patients at home [8,[27][28][29][30][31], insurance bodies in many countries including Switzerland incomprehensibly require personal consultations for coverage of costs. More studies are needed to investigate whether telemedicine approaches can supplement traditional patient care [27,32] and personal training.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that confinement and reduced medical services affect psychiatric health [3] but may also worsen progression of chronic diseases such as PD has consequences for the decision-making process of lawmakers and governmental bodies. Further, whilst treatments for improving functional outcomes through telemedicine offer opportunities to treat patients at home [8,[27][28][29][30][31], insurance bodies in many countries including Switzerland incomprehensibly require personal consultations for coverage of costs. More studies are needed to investigate whether telemedicine approaches can supplement traditional patient care [27,32] and personal training.…”
Section: Discussionmentioning
confidence: 99%
“…After the new era of pandemic emergencies, telehealth systems have become a fundamental service for pursuing and maintaining healthcare protocols. In neurological diseases, such as Parkinson’s [ 1 , 2 ]; Alzheimer’s [ 3 , 4 ] and Multiple Sclerosis [ 5 , 6 ], a large number of tools and services have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The restrictions in social contact and participation imposed in response to the COVID-19 pandemic significantly impacted older people, many of whom faced the highest levels of isolation because of the age-related risk factors associated with the virus [29,30]. In these circumstances, the importance of telehealth [31][32][33] and digital alternatives such as apps and online programs for maintaining communication and activity [33,34] was brought to the forefront. Older people are increasingly confident in using digital technology, and studies during the pandemic reported that digital resources were used by older adults to maintain social connections [35] and by people with PD to engage in physical activity [32,36].…”
Section: Introductionmentioning
confidence: 99%